Evidence and speculations: vaccines and therapeutic options for COVID-19 pandemic. Issue 4 (3rd April 2021) - Siddique, Rabeea; Bai, Qian; Shereen, Muhammad Adnan; Nabi, Ghulam; Han, Guang; Rashid, Farooq; Ahmed, Saeed; Benzhanova, Aigerim; Xue, Mengzhou; Khan, Suliman
ABSTRACT: A novel coronavirus (2019-nCov) emerged in China, at the end of December 2019 which posed an International Public Health Emergency, and later declared as a global pandemic by the World Health Organization (WHO). The International Committee on Taxonomy of Viruses (ICTV) named it SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2), while the disease was named COVID-19 (Coronavirus Disease- 2019). Many questions related to the exact mode of transmission, animal origins, and antiviral therapeutics are not clear yet. Nevertheless, it is required to urgently launch a new protocol to evaluate the side effects of unapproved vaccines and antiviral therapeutics to accelerate the clinical application of new drugs. In this review, we highlight the most salient characteristics and recent findings of COVID-19 disease, molecular virology, interspecies mechanisms, and health consequences related to this disease.